Marketing strategy of the Church in Russian Federation - Myasnikova, Valeriya; Průša, Přemysl, 1980-; Asmalovskij, Alexandr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This bachelor thesis introduces in the beginning the basic theory of marketing.The second part presents theoretical framework of the Church.The final part consists of defining if the Russian Orthodox Church can be called a business company, the possibility of use marketing strategies by religious organizations, creating marketing mix for the church and the survey.
Vedoucí práce: Přemysl Průša
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses